Tax Service Satisfaction Analysis Using the Servqual Method - Importance and Performance Analysis at the Regional Revenue Agency of Jeneponto Regency - Muhammad Nusran; Muh. Irsal Hidayat; Anis Saleh (PT FORMOSA CENDEKIA GLOBAL, 2024)
Service quality plays a crucial role in shaping the public's positive perception. This study applies the